Customer experience in omni-channel banking services. Issue 3 (December 2018) - Komulainen, Hanna; Makkonen, Hannu
Abstract The banking industry is experiencing rapid and widespread changes due to advances in technology that go hand-in-hand with the customer demands for real-time, personalized and seamless banking experience. Along with this development, omni-channel orientation is becoming an inherent feature of banking services. However, its role has not yet been thoroughly understood, specifically in this context. The purpose of this study is to create in-depth understanding of how do customers experience omni-banking services and what are the key factors related to their experiences. We identify both actual critical events and imaginings, positive and negative that are related to the forming of customer experiences and suggest both theoretical and managerial implications based on the results.